Sociodynamics applied to the evolution of urban and regional structures - Wolfgang Weidlich (Discrete Dynamics in Nature and Society)
The article consists of two parts. In the first section the concepts of sociodynamics are briefly explained. Sociodynamics is a general modelling strategy for the quantitative description of dynamic processes in the human society. The central concepts of sociodynamics include transition rates depending on dynamic utilities and the master equation for the probability distribution over macrovariables. From it the set of nonlinear coupled differential equations for the quasi-meanvalues of the macrovariables can be derived.